2020
DOI: 10.1002/epa2.1089
|View full text |Cite
|
Sign up to set email alerts
|

Claiming credit and avoiding blame: political accountability in Greek and Turkish responses to the COVID‐19 crisis

Abstract: In this article, we focus on political accountability by comparing the Greek and Turkish national responses to the COVID-19 crisis. The study is underpinned by the assumption that the overarching objective of all leaders is re-election (Mayhew, 2004). Policymakers' failure to tackle the crisis may not only have devastating consequences for the lives and well-being of citizens, but also for their prospects for re-election (Boin, 't Hart, Stern, & Sundelius, 2017; Brändström, 2016). Conversely, success involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
6

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
(30 reference statements)
0
27
0
6
Order By: Relevance
“…For a considerable period in the second half of March 2020, Switzerland had the highest infection rate per 1,000 people worldwide, ahead even of China and Italy (Gal & Woodward, 2020). Regardless of the variations in measurement methods across the world and their accuracy, these numbers indicated that Switzerland was hit hard when compared to other countries even though not as hard as other countries like Italy (Malandrino & Demichelis, 2020; Petridou et al., 2020; Zahariadis et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For a considerable period in the second half of March 2020, Switzerland had the highest infection rate per 1,000 people worldwide, ahead even of China and Italy (Gal & Woodward, 2020). Regardless of the variations in measurement methods across the world and their accuracy, these numbers indicated that Switzerland was hit hard when compared to other countries even though not as hard as other countries like Italy (Malandrino & Demichelis, 2020; Petridou et al., 2020; Zahariadis et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although by this time government communication had been dominated by the pandemic response, no other policymaker than the prime minister emerged as a key decision maker in relation to the crisis. This was in contrast to the practice of a number of liberal democratic governments that placed high-profile civil servants with a technocratic profile or highly esteemed experts in the forefront of government communication on the pandemic (see Colfer, 2020;Zahariadis et al, 2020). This way, elected officials could distance themselves from expert-opinion-based decisions and could limit the political risk of concomitant measures.…”
Section: Crisis Responsementioning
confidence: 99%
“…Meanwhile in Ireland, technocrats were to the fore, as responsibility for delivering government communications around the pandemic was fulfilled almost exclusively by senior medical advisors, many of whom are now household names, and with the Taoiseach and senior government ministers making only rare set piece interventions throughout the crisis. Zahariadis et al (2020) also review the role of experts under COVID-19, specifically with respect to Greece and Turkey.…”
Section: Risk and Evidencementioning
confidence: 99%